Pengetahuan Anak Pra Sekolah tentang Pencegahan Stunting - Budi Astyandini; Ana Sundari; Rina Budiningtyas (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Stunting is a global and national health problem. Stunting is a toddler with chronic nutritional problems. Prenatal age is referred to as the golden period in growth and development, this age is a critical period that requires food with better quantity and quality compared to adults. Prenatal age is referred to as the golden period in growth and development, this age is a critical period that requires food with better quantity and quality compared to adults. This type of research is quantitative research with a descriptive observational approach, which was carried out with a population of preschool children in Muslimat 02 Bandengan Kindergarten, Kendal District, totaling 30 students. The results show that the majority of respondents already know about healthy food, namely 11 children (37%), the majority of children have sufficient knowledge, namely 12 people (40%) about the body characteristics of children who are stunted, and the majority of children have Good knowledge about personal hygiene was 15 children (50%). The role of teachers, parents and midwives in providing health education and habituation to healthy lifestyles to prevent stunting needs to be increased so that pre-school children's knowledge increases.